This preview shows pages 1–3. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: MAD 6206 Combinatorics I, Fall 2011 CRN: 87401 On Gosper’s Algorithm The aim is to find a simple form for the sum S ( m ) = ∑ m n =0 t n where r ( n ) = t n +1 /t n is a rational function of n . That is, t n is a hypergeometric term in n and does not depend on m . 1 A Brief Description The idea is find a hypergeometric term z n such that z n +1 − z n = t n , (1) and the sum is therefore S ( m ) = z m +1 − z . To find z n , we write y ( n ) = z n t n = 1 z n +1 z n − 1 , where since z n is a hypergeometric term, we see that y is a rational fucntion, and the problem is turned into finding a rational function y ( n ) where from (1), y ( n + 1) r ( n ) − y ( n ) = 1 . (2) The main step is to find functions a ( n ) ,b ( n ) and c ( n ) (with some required properties to be stated later) so that r ( n ) = t n +1 t n = a ( n ) b ( n ) c ( n + 1) c ( n ) , (3) and (2) now becomes c ( n + 1) y ( n + 1) a ( n ) b ( n ) − y ( n ) c ( n ) = c ( n ) . Writing x ( n ) = c ( n ) y ( n ) b ( n − 1) , or y ( n ) = b ( n − 1) x ( n ) c ( n ) , the previous recurrence in y becomes a recurrence in a rational function x : a ( n ) x ( n + 1) − b ( n − 1) x ( n ) = c ( n ) Now the functions a,b,c in (3) are chosen so that x is a polynomial in n . The first order recurrence in x is then solved (if possible), and hence z n = y ( n ) t n = b ( n − 1) x ( n ) c ( n ) t n . (4) 2 The functions a, b, c Theorem 1. Let r be a rational function over a field K with characteristic zero. Then there are polynomials a,b,c over K such that b,c are monic and r ( n ) = a ( n ) b ( n ) c ( n + 1) c ( n ) , where (i) gcd( a ( n ) ,b ( n + h )) = 1 for all integer h ≥ , (ii) gcd( a ( n ) ,c ( n )) = 1 , (iii) gcd( b ( n ) ,c ( n + 1)) = 1 Proof. Suppose that r ( n ) = f ( n ) g ( n ) , where f,g are polynomials in n over K . We can assume that g is monic and that gcd( f ( n ) ,g ( n )) = 1. If there does not exist h > 0 such that gcd( f ( n ) ,g ( n + h )) = 1, then take a = f , b = g and c = 1 and we are done. Otherwise let h be the smallest positive integer such u ( n ) = gcd( f ( n ) ,g ( n + h )) is not a constant . Now u ( n ) ,u ( n − h ) respectively are divisors of f ( n ) and g ( n ), and we write f ( n ) = u ( n ) f 1 ( n ) , g ( n ) = u ( n − h ) g 1 ( n ) , c 1 ( n ) = h productdisplay i =1 u ( n − i ) , giving that r ( n ) = f ( n ) g ( n ) = f 1 ( n ) g 1 ( n ) × u ( n ) u ( n − 1) ··· u ( n − h + 1) u ( n − 1) n ( n − 2) ··· u ( n − h ) = f 1 ( n ) g 1 ( n ) c 1 ( n + 1) c 1 ( n ) . By the minimality of h , we see that gcd( f 1 ( n ) ,c 1 ( n )) = 1 , gcd( g 1 ( n ) ,c 1 ( n + 1)) = 1 . If gcd( f 1 ( n ) ,g 1 ( n )) = 1 then we are done, else we can repeat the above process for f 1 ( n ) and g 1 ( n )....
View
Full
Document
 Spring '11
 Suen

Click to edit the document details